2014
DOI: 10.1016/j.ijpara.2014.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Vaccines to combat river blindness: expression, selection and formulation of vaccines against infection with Onchocerca volvulus in a mouse model

Abstract: Human onchocerciasis is a neglected tropical disease caused by Onchocerca volvulus and an important cause of blindness and chronic disability in the developing world. Although mass drug administration of ivermectin has had a profound effect on control of the disease, additional tools are critically needed including the need for a vaccine against onchocerciasis. The objectives of the present study were to: (i) select antigens with known vaccine pedigrees as components of a vaccine; (ii) produce the selected vac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
72
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(78 citation statements)
references
References 70 publications
5
72
1
Order By: Relevance
“…While their exact role in O. volvulus is not clear, the expression of polyglutamine repeats was shown to be neurotoxic in both C. elegans and Drosophila and is dynamically regulated throughout the lifetime of an organism, suggesting a link to longevity (15). Interestingly, one of the lead O. volvulus vaccine candidates (16), Ov-RAL-2 (OVOC9988), has 11 glutamine residues in its amino terminus. These residues are probably not important for the protective ability of this protein, as the Brugia malayi homologue (Bm2001), that is also protective in animals, does not have this repeat (17).…”
Section: Resultsmentioning
confidence: 99%
“…While their exact role in O. volvulus is not clear, the expression of polyglutamine repeats was shown to be neurotoxic in both C. elegans and Drosophila and is dynamically regulated throughout the lifetime of an organism, suggesting a link to longevity (15). Interestingly, one of the lead O. volvulus vaccine candidates (16), Ov-RAL-2 (OVOC9988), has 11 glutamine residues in its amino terminus. These residues are probably not important for the protective ability of this protein, as the Brugia malayi homologue (Bm2001), that is also protective in animals, does not have this repeat (17).…”
Section: Resultsmentioning
confidence: 99%
“…Based on successful results using animal models, some candidate vaccines against onchocerciasis have been found [105,106] and further trials are planned. The potential deployment of a vaccine has been modelled and it was concluded that after 15 years of a childhood vaccination programme it would have a protective effect and be valuable for preventing re-emergence of the disease in areas cleared of the infection [107].…”
Section: Vaccines For Onchocerciasismentioning
confidence: 99%
“…Based on a mouse‐ Onchocerca model, the top ranking eight Ov protective antigens ( Ov ‐CPI‐2, Ov ‐ALT‐1, Ov ‐RAL‐2, Ov ‐ASP‐1, Ov ‐103, Ov ‐RBP‐1, Ov ‐CHI‐1, and Ov ‐B20) were chosen for more extensive studies . Using two model systems, O. volvulu in mice and Brugia malayi in gerbils, this list of candidates has been reduced to the final selection of Ov ‐103 and Ov ‐RAL‐2 for further clinical development …”
Section: Introductionmentioning
confidence: 99%